Correlation between superconductivity and structure in the [Y1−xPrx]Ba2Cu3O7 system - Flores, Jesús (2011)
A structural study of the incorporation of Pr-ion into the Y-site was realized in polycrystalline samples of [Y1−xPrx]Ba2Cu3O7 through of Rietveld analysis of X-ray diffraction patterns, bond valence method and electronic density diagrams correlating its doping effects on the superconducting properties. The oxygen content was checked by means of μ-Raman spectroscopy, observing the frequency position of OO4-Ag phonon mode, and establishing a relationship among the O4-Ag mode frequency and the two copper sites, Cu(1) and Cu(2). Two regions are observed with Pr-rich and Y-rich microstructures.